A novel HLA‐DRB1 allele, DRB1*01:54, identified by sequence‐based typing. Issue 1 (18th April 2013) - Barbuti, S.; Curcio, M.; Marchetti, L.; Vittorio, O.; Mariotti, M. L; Scatena, F.
<x xml:space="preserve">Abstract</x> The new HLA DRB1*01:54 differs from DRB1*01:02:01 by one nucleotide at exon 2.